2014
DOI: 10.1002/hed.23760
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms in newly diagnosed patients with head and neck cancer and their partners

Abstract: Background Head and neck cancer is a life threatening illness requiring aversive treatments. Despite clear potential for posttraumatic stress disorder (PTSD) symptoms in both patients and their partners, research is scant. Methods Newly diagnosed patients and partners (no. of dyads=42) completed questionnaires to assess symptoms of PTSD, anxiety, and depression, as well as demographic, medical, and attitudinal variables. Results Partners had higher average levels of PTSD symptoms than patients (p=.023). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 41 publications
5
47
3
Order By: Relevance
“…Our results corroborate previous findings that clinicians need to be aware of PTSD symptoms in not only HNC patients but also their caregivers [6]. This is particularly important in light of evidence that caregiver distress influences patient outcomes [41,42].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results corroborate previous findings that clinicians need to be aware of PTSD symptoms in not only HNC patients but also their caregivers [6]. This is particularly important in light of evidence that caregiver distress influences patient outcomes [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…Results showed that 19 % of caregivers met criteria for estimated PTSD caseness 6 months after HNC diagnosis. This rate is slightly lower than the 29 % reported in HNC caregivers between 4 and 16 weeks after HNC diagnosis [6], which is an earlier timeframe. The presence of PTSD symptoms at 6 months is consistent with the growing literature demonstrating high rates of psychological distress in HNC caregivers across the disease trajectory [3], as well as in caregivers of patients with other cancer types [26][27][28].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations